2015
DOI: 10.1016/j.jssr.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Where is the Content?: Elementary Social Studies in Preservice Field Experiences

Abstract: Anecdotal evidence has long lamented the status of social studies in elementary classrooms as observed by preservice teachers. As standardized testing has risen for mathematics and language arts, social studies has been pushed aside. In the aftermath of accountability legislation such as No Child Left Behind, research indicates that social studies is less visible in elementary classrooms due to an instructional focus on tested content areas (e.g. math, language arts, reading). In this study, approximately 90 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Preservice elementary teacher candidates in the United States have reported fewer social studies experiences (coursework and fieldwork) in comparison to other subject matter (Hawkman, Castro, Bennett, & Barrow, 2015), which makes sense given the lack of attention to social studies in U.S. elementary classrooms. Presumably, if the subject is disappearing from classrooms, preservice teachers have fewer opportunities to see good social studies instruction or practice delivering it in a field practicum.…”
Section: Social Studies In Us Elementary Schoolsmentioning
confidence: 99%
“…Preservice elementary teacher candidates in the United States have reported fewer social studies experiences (coursework and fieldwork) in comparison to other subject matter (Hawkman, Castro, Bennett, & Barrow, 2015), which makes sense given the lack of attention to social studies in U.S. elementary classrooms. Presumably, if the subject is disappearing from classrooms, preservice teachers have fewer opportunities to see good social studies instruction or practice delivering it in a field practicum.…”
Section: Social Studies In Us Elementary Schoolsmentioning
confidence: 99%
“…Within the field of history education, there are numerous studies that focused on the development of inquiry-based instruction during preservice teacher preparation (Baron, Woyshner, & Haberkern, 2014; Barton, McCully, & Marks, 2004; Hawkman, Castro, Bennett, & Barrow, 2015; Levy et al, 2013; Martin & Monte-Sano, 2008; Mayer, 2006; Seixas, 1998; van Hover & Yeager, 2004; Yeager & Wilson, 1997) or the use of inquiry-based instruction by experienced or exemplary teachers (Grant, 2001; Monte-Sano, 2008; Reisman, 2012; Voet & Wever, 2016). Across these studies, there were two main findings.…”
Section: Relevant Literaturementioning
confidence: 99%
“…However, some research works suggest that not much has changed in the wake of CCSS. For instance, Hawkman et al (2015) found that 67 percent of preservice elementary teachers observed two or fewer social studies lessons over the course of an entire semester. Additionally, Denton and Sink (2015) found that integration with literacy instruction remains teachers’ preferred method of delivering social studies content.…”
Section: Literature Reviewmentioning
confidence: 99%